PENINGKATAN KUALITAS KELUARGA DENGAN PEMASANGAN IUD DAN IMPLANT DI PMB CATUR ENI PRIHATIN.,S.ST.,BDN - Wulandari, Amri; Krismiyati, Murti; Putrianti, Berlina (LPPM Politeknik Kesehatan Karya Husada Yogyakarta, 2023)
The population growth rate indicates an explosion in Indonesia's population if there is no family planning program. Programs carried out by the government to reduce the population rate with the Family Planning movement and the voluntary use of contraceptives to couples of childbearing age (PUS). The family planning movement is carried out to build a prosperous family in order to create optimal human resources. Family planning programs are one of the most effective ways to improve family resilience, health, and safety of mothers, children and women. Objective: Increase the scope of use of IUD contraceptives and implants, practice methods and counseling. Couples of childbearing age who participated in community service activities totaled 18 participants, with the results of acceptors who used implants totaling 11 PUS (61.11%), and IUDs totaling 7 PUS (38.89%), participants aged 20-35 years as many as 9 (50%), and age >35 years as many as 9 (50%), junior high school education level 3 participants (16.67%), high school 14 participants (77.78%), higher education 1 participant (5.56%), parity ≤ 2 as many as 10 (55, 56%), and >2 namely 8 participants (44, 46%) After installation activities, and counseling participants understand how to post-install contraceptive care.